Case Report: Infantile Ischemic Stroke and Antiphospholipid Antibodies, Description of Four Cases - Giani, Teresa; Mauro, Angela; Ferrara, Giovanna; Cimaz, Rolando (Frontiers in Pediatrics, 2020)
Antiphospholipid syndrome (APS) is a rare condition in childhood, but even more in the neonatal age. Most neonatal cases are considered a passively acquired autoimmune disease, due to a transplacental passage of maternal antiphospholipid antibodies (aPL) from mothers with primary or secondary APS or, more often, from asymptomatic aPL carriers. Exceedingly unusual is the neonatal de novo production of aPL. We present four infants with presumed perinatal stroke in presence of increased and persistent aPL levels, even after six months of life, opening the window on a gray zone related to the origin of these antibodies (maternal or neonatal) and on their role in the pathogenesis of stroke.